Governing stem cell therapy in India: regulatory vacuum or jurisdictional ambiguity? - Tiwari, Shashank S.; Raman, Sujatha (Taylor & Francis, 2014)
Stem cell treatments are being offered in Indian clinics although preclinical evidence of their efficacy and safety is lacking. This is attributed to a governance vacuum created by the lack of legally binding research guidelines. By contrast, this paper highlights jurisdictional ambiguities arising from trying to regulate stem cell therapy under the auspices of research guidelines when treatments are offered in a private market disconnected from clinical trials. While statutory laws have been strengthened in 2014, prospects for their implementation remain weak, given embedded challenges of putting healthcare laws and professional codes into practice. Finally, attending to the capacities of consumer law and civil society activism to remedy the problem of unregulated treatments, the paper finds that the very definition of a governance vacuum needs to be reframed to clarify whose rights to health care are threatened by the proliferation of commercial treatments and individualized negligence-based remedies for grievances.